Efficacy and safety of CO2 cryotherapy in the treatment of infants with tracheobronchial tuberculosis - Zhao, Yidi; Zhang, Tongqiang; Yang, Nan; Xu, Yongsheng; Guo, Wei (Frontiers in Pediatrics, 2022)
Objective: The aim of the study was to investigate the efficacy and safety of CO2 cryotherapy for lymph node fistula tracheobronchial tuberculosis (TBTB) in infants. Patients and methods: Retrospective analysis was performed in 7 patients with lymph node fistula tracheobronchial tuberculosis treated with fiberoptic bronchoscopy(FB) interventional therapy in the respiratory department of Tianjin Children's Hospital from July 2012 to July 2020. The efficacy, safety and prognosis of the CO2 cryotherapy intervention for the treatment of lymph node fistula TBTB in infants was summarized and analyzed. Results: The median age of the patient was 8 months (6 months to 13 months), with 6 cases were males. The course of disease from onset to TBTB ranging from 20d to 70 d. The pathological diagnosis of 7 cases by FB combined with tissue biopsy was lymph node fistula TBTB, of which 28.57% (2 cases) were in the early stage of rupture and 71.43% (5 cases) were in the stage of rupture. All the patients were treated with CO2 cryotherapy combined with foreign body forceps and local injection drugs based on systemic antituberculosis chemotherapy. There was no obvious bleeding, airway spasm and other complications found during and after the operation. The clinical symptoms of all patients were relieved after first interventional treatment. 2 patients were treated once for CO2 cryotherapy and 5 patients were 3 times. 6 patients achieved clinical cure, and 1 patients achieved clinical improvment. Computed Tomography(CT) and FB was reexamined after 3 months of first interventional treatment. All patients showed significant improvement in hilar and mediastinal enlargement, calcified lymph nodes, bronchial obstruction, emphysema, and pulmonary atelectasis compared with those before the intervention in lung CT. The FB showed that the fistula was basically closed, the bronchial lesions was significantly absorbed and improved, the lumen stenosis or obstruction was reduced, and the bronchial mucosa was relatively smooth. There was no recurrence after 3-6 months of follow-up using FB. Conclusion: CO2 cryotherapy can improve the treatment effect of lymph node fistula TBTB in infants and reduce the incidence of complication. This treatment is safe and reliable in infants.